(untitled) (Scientific journal of the Fergana State University, 2025)
In this article, over the past thirty years, through the reforms implemented in the issue of ensuring the health of conscripts reducing the sending of unfit teenagers to the ranks of the army, by constantly monitoring the health of teenagers, the ranks of the Armed Forces are discussed. it is analyzed whether the provision of healthy personnel has been achieved.